Thermally reversible rubber-toughened thermoset networks via Diels–Alder chemistry. (January 2016) - Araya-Hermosilla, R.; Fortunato, G.; Pucci, A.; Raffa, P.; Polgar, L.; Broekhuis, A.A.; Pourhossein, P.; Lima, G.M.R.; Beljaars, M.; Picchioni, F.
Graphical abstract: Highlights: Toughened thermosets were prepared via Diels–Alder reversible cross-linking. Furane functionalized EPM and PK were crosslinked with bismaleimide. Thermo-mechanical experiments indicated the re-workability of the material. A substantial increase in the softening point was found for the higher toughened system. A two-fold increase in impact strength was recorded compared to the neat thermoset. Abstract: In this work we present a reversible and toughened thermoset system based on the covalent incorporation of a furane functionalized ethylene–propylene rubber (EPM-Fu) into a thermoset furane functionalized polyketone (PK-Fu) via Diels–Alder (DA) reversible cross-linking with bismaleimide (b-MA). FT-IR and DSC analyses proved the reversible interaction between PK-Fu and EPM-Fu with b-Ma via DA and r-DA sequence. Likewise, thermo-mechanical experiments (DMTA) indicated the re-workability of the material with no evident differences in elastic and loss modulus after several heating cycles and recycling procedures. Moreover, a considerable increase in the softening point (tangent  δ ) was also found for the higher toughened system containing 12 wt% of EPM-Fu (neat thermoset T  = 137 °C whereas toughened thermoset T  = 155 °C). A two-fold increase in IZOD impact strength compared to the neat thermoset (up to 27 J/m) was also recorded by the toughened system. Overall, this approach clearly indicates that fully thermally reversible and toughened thermosets can be realized starting from mixtures of furan functionalized polyketone and EPM rubber, cross-linked via reversible Diels–Alder chemistry.